INNOVATION ANALYSIS AJI WELAS (DEED SO IF THE APPLICANT ENTERS BEFORE SEWELAS HOURS) DEPARTMENT OF POPULATION AND CIVIL REGISTRATION SEMARANG DISTRICT - Islamiyati, Dian Nur; Maesaroh, Maesaroh; Widowati, Nina (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2021)
Semarang regency has a high population. This increase in population influences the high demand for population administration services, one of which is birth certificates. The length of the process of issuing birth certificates resulted in people being lazy to take care of themselves and preferring touts. This resulted in many people who do not have a birth certificate. Aji Welas innovation was created to complement previous innovations with a faster birth certificate issuance service which is one anniversary and expand the scope of birth certificate ownership in Semarang Regency. The purpose of this study is to analyze the attribute innovation and the factors that become the drivers and inhibitions of innovation. This study uses a qualitative method with a descriptive approach. The theory in this study uses the theory of Rogers, while the driving and inhibitory factors of Albury to know the characteristics and implementation of aji welas innovation. The results showed that Aji Welas innovation has 1) relative advantage, 2) conformity, 3) possibility of trying, 4) ease of observing, 5) complexity. In the implementation of innovation, Aji Welas has supporting factors, namely adequate human resources, and also supporting infrastructure facilities. In addition, in the implementation, there are also inhibitory factors, namely not budgeted for the implementation of socialization, constrained networks that often error or trouble, there are still many people who do not complete the document requirements when applying, and some innovation implementing officers Aji Welas who concurrently task. The advice given by researchers is that it is necessary to submit a budget for socialization, increase the strength of the network or wifi, encourage creative innovation publications, and recruit PPPK (Government Employees with Employment Agreements).